2017
DOI: 10.3892/mmr.2017.6612
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA AB019562 promotes cell proliferation and metastasis in human hepatocellular carcinoma

Abstract: Increasing evidence has supported the prognostic and therapeutic values of long non-coding RNAs (LncRNAs) in human tumorigenesis. Hepatocellular carcinoma (HCC), as one of the most refractory diseases, continues to warrant investigation for novel clues to enable early diagnosis. In the present study, the role of LncRNA AB019562 in cell proliferation and metastasis was investigated in HCC. Reverse transcription-quantitative polymerase chain reaction analysis was performed to determine the expression of AB019562… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The lncRNA elevation often facilitates HCC progression [ 25 ]. The expression of lncRNAs, such as MALAT1 [ 10 ], AB019562 [ 24 ], and CARLo-5 [ 26 ], is enhanced in HCC patients. In the present research, MIR100HG expression was elevated in HCC, indicating that MIR100HG may be an oncogenic lncRNA in HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lncRNA elevation often facilitates HCC progression [ 25 ]. The expression of lncRNAs, such as MALAT1 [ 10 ], AB019562 [ 24 ], and CARLo-5 [ 26 ], is enhanced in HCC patients. In the present research, MIR100HG expression was elevated in HCC, indicating that MIR100HG may be an oncogenic lncRNA in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR and western blot were performed as previously described [ 24 ]. The primers are depicted in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TINCR lncRNA is found to be upregulated in HCC cells acting as an oncogene regulating differentiation, invasion and metastasis of tumor cells[ 61 ]. AB019562 is reported to be upregulated in HCC cells; its knockdown inhibits cell proliferation, arrests cell cycle at G0/G1 phase, suppresses cellular metastasis, induces apoptosis and activates caspase-3 activity[ 62 ]. LncARSR is a long non-coding RNA that regulates the sensitivity of the tumor cells to doxorubicin.…”
Section: Lncrna In Hccmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are non-protein coding RNAs that are greater than 200 nucleotides in length (3). Numerous studies have indicated that lncRNAs are capable of regulating gene expression at the transcriptional, post-transcriptional and epigenetic levels, and serve an important role in human cancer development, prognosis and drug resistance (4,5). Recent studies have associated certain lncRNAs, including CCAT1 (6) and TRPM2-AS (7), with DDP resistance in lung cancer.…”
Section: Introductionmentioning
confidence: 99%